1992
DOI: 10.1159/000227069
|View full text |Cite
|
Sign up to set email alerts
|

Primary Small Intestinal Lymphoma

Abstract: Gastro-intestinal tract is the most common site of extranodal presentation in non-Hodgkin’s lymphoma. Among the subsites the small intestine predominates. This paper presents a review of 21 cases of primary gastro-intestinal lymphoma seen at the Department of Radiation Oncology, Christian Medical College, Vellore, during the period 1979-1986. All patients had laparotomy, and biopsy from the primary site. Histopathological subtypes were done in the International Working Formulation. Stage groupings were done ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…Patients with bowel obstruction and intestinal perforation also need surgery. Therefore, patients with primary intestinal NHL received surgery with postoperative chemotherapy and/or radiotherapy [26,27]. Previous retrospective studies have found that radical surgery was helpful for survival.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with bowel obstruction and intestinal perforation also need surgery. Therefore, patients with primary intestinal NHL received surgery with postoperative chemotherapy and/or radiotherapy [26,27]. Previous retrospective studies have found that radical surgery was helpful for survival.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the difficulty of accurate diagnosis and the potential for initial complications, in most cases of small bowel lymphoma the main tumour is surgically resected. 13,14 After the operation, not only can the histological diagnosis of the lymphomas be established but accurate staging can also be made. Chemotherapy and radiotherapy have been used alone or in combinations and in combination with surgery, 15 however the results have not been evaluated adequately and the efficacy of these procedures is not known.…”
Section: Introductionmentioning
confidence: 99%
“…La afectación por linfomas de células T es menos frecuente y tiene presentación heterogénea (6, 7). Se ha dicho clásicamente que el sitio más frecuente de linfoma gastrointestinal es el estómago, seguido por el intestino delgado, colon, ciego, esófago y afectación múltiple (8,9); sin embargo, Ha encontró en su revisión de 61 casos que la afectación del intestino delgado estaba presente del 20% al 54% de los linfomas gastrointestinales primarios (10). El sitio menos frecuente es el recto (11).…”
Section: Discussionunclassified